2017
DOI: 10.1007/s10620-017-4768-7
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Therapy of Biliary Injury After Cholecystectomy

Abstract: After the right patient selection, the success rate of endoscopic treatment can approach 100% for Amsterdam type A bile leak. ES is an effective and cost-effective single procedure with success rate similar to EST. It may be considered as a first-line therapy for the management of Amsterdam type A leaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 24 publications
1
30
0
10
Order By: Relevance
“…Sphincterotomy and plastic stent placement with ERCP are usually sufficient in patients who have an intact tract and do not have signs of peritonitis. [17] Therefore, laparotomy should not be performed unless the injury is properly classified. [17] According to the European Society of Gastrointestinal Endoscopy (ESGE) clinical guideline, partial divisions of ducts can be successfully treated endoscopically in more than 90% of the cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphincterotomy and plastic stent placement with ERCP are usually sufficient in patients who have an intact tract and do not have signs of peritonitis. [17] Therefore, laparotomy should not be performed unless the injury is properly classified. [17] According to the European Society of Gastrointestinal Endoscopy (ESGE) clinical guideline, partial divisions of ducts can be successfully treated endoscopically in more than 90% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Therefore, laparotomy should not be performed unless the injury is properly classified. [17] According to the European Society of Gastrointestinal Endoscopy (ESGE) clinical guideline, partial divisions of ducts can be successfully treated endoscopically in more than 90% of the cases. [18] Also, Jabłonska et al reported that endoscopic interventions had a 93% success rate, especially in type A and D injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Основным принципом восстановления ЖП является мобилизация двенадцатиперстной кишки (ДПК) с частичной мобилизацией сшиваемых концов ЖП без натяжения, использование прецизионной техники и атравматичных нитей 5/0-6/0 [1,16]. В медицинской литературе описано большое число приемов, используемых для восстановления ЖП при их повреждении [1,[17][18][19], с наложением билиодигестивных анастомозов (БДА) с ДПК [7,8] или с тонкой кишкой [21][22][23] при невозможности восстановления непрерывности ЖП с протяженными дефектами. Принципы выполнения БДА соответствуют принципам наложения билиобилиарных соустий.…”
Section: Introductionunclassified
“…Поздняя диагностика ранений с развитием механической желтухи и перитонита требует наружного дренирования ЖП без восстановительных и реконструктивных операций вследствие опасности формирования рубцовых стриктур в условиях воспаления [7,10]. В настоящее время при возникновении повреждений ЖП широко используют методы эндоскопической декомпрессии и стентирования [23].…”
Section: Introductionunclassified
“…In this issue of Digestive Diseases and Sciences, Ranio et al [10] report a retrospective analysis of patients referred to Helsinki University Hospital for endoscopic therapy of Amsterdam type A biliary leaks (leak from cystic duct or peripheral radicals). The authors reported no difference in the closure of leaks between those treated with sphincterotomy alone versus those with sphincterotomy plus stent placement.…”
mentioning
confidence: 99%